Consecuencias de la inteligencia emocional: Competencia gerencial, liderazgo transformacional y desempeño de gestores de oficinas de contabilidad - Oliveira, Rosana Santos de (2025)
Emotional intelligence has become a key element in management, especially in contexts that require strategic decision-making, such as accounting firms. The ability to manage emotions, understand others’ needs, and establish constructive relationships is essential for managers to face challenges related to competence, leadership, and performance in dynamic environments. Based on this premise, the study aimed to analyze the influence of emotional intelligence on managerial competence, transformational leadership, and the performance of accounting firm managers. Previous studies have shown that emotional intelligence can positively impact both managerial competence (Aslam et al., 2016; Kour & Ansari, 2024) and transformational leadership (Lee et al., 2022). The research was conducted through a questionnaire administered to managers of accounting firms registered with the Regional Accounting Council of Santa Catarina, resulting in 108 responses that allowed for hypothesis testing. For data analysis, the partial least squares structural equation modeling (PLS-SEM) technique was used. The results indicate a positive and significant relationship between emotional intelligence and managerial competence, as well as between emotional intelligence and transformational leadership. Additionally, a positive relationship was found between managerial competence and transformational leadership, as well as between managerial competence and managerial performance. Finally, the findings suggest that transformational leadership positively influences managerial performance. These results highlight the importance of investing in the development of emotional intelligence, managerial competence, and transformational leadership to prepare managers to achieve better managerial performance.